HERMAPHRODITISM IN THE THREADFIN FISH, POLYNEMUS MICROSTOMA BLEEKER - Dorairaj, K (Indian Journal of Fisheries, 2011)
The occurrence of hermaphroditism in the small-mouthed thrcadfin fish, Polynemus microstoma Bleeker, collected from the Palk Bay and the Gulf of Mannar is reported for the first time. Hermaphroditism is found in both the lobes of the gonad. The two sex portions in the ovotestis, which are easily distinguishable by their colpur, adhere along the entire length of the gonad in antero-posterior direction. The testicular portion is on the inner lateral side of the gonad. The relative size of the male and female portions of the ovotestis varies in different specimens. It is seen from the microsections that the two sex portions are separated by a thin connective tissue.